Development of different technical, economic and financial benchmarks as management tool for intensive milk producers on the Highveld of South Africa - Coetzee, Koos (University of Pretoria, 2013)
Dissertation (MSc (Agric): Agricultural Economics)--University of Pretoria, 2008.